Sevoflurane anesthesia impairs metabotropic glutamate receptor‐dependent long‐term depression and cognitive functions in senile mice. Issue 4 (17th February 2019) - Yu, Xiangdi; Zhang, Fangxiang; Shi, Jinshan
Abstract : Aim: Postoperative cognitive dysfunction is often observed in older patients. Previous reports described the link between postoperative cognitive dysfunction and general anesthetics, such as sevoflurane, but the exact mechanism remains unclear. We therefore sought to characterize the effects of sevoflurane on hippocampal‐dependent cognitive functions, as well as hippocampal plasticity, and to delineate the underlying mechanisms. Methods: Behavioral assays including the novel object recognition test and the Morris water maze test were carried out to assess the cognitive performance of control and sevoflurane‐exposed mice. Electrophysiological recordings were carried out to evaluate the sevoflurane‐induced changes of synaptic plasticity in the hippocampus. Furthermore, western blot assay was utilized to quantitatively assess the altered protein expression resulting from sevoflurane exposure. Results: Sevoflurane anesthesia impaired cognitive functions, as well as metabotropic glutamate receptor‐dependent long‐term depression, through elevated surface expression of small conductance calcium‐activated potassium type 2 channels. Blockage of calcium‐activated potassium type 2 channels reversed the sevoflurane‐induced deficits at both cellular and behavioral levels. Conclusions: Sevoflurane anesthesia impaired metabotropic glutamate receptor‐dependent long‐term depression and thereby affected cognitive functions in old mice. Inhibitory modulators of calcium‐activated potassium type 2 channels might prevent cognitive decline elicited by sevoflurane. Geriatr Gerontol Int 2019; 19: 357–362 .